Sistem Penentuan Lokasi dan Penyimpanan Barang Menggunakan LabVIEW dan Sensor Ultrasonik - Artdhita Fajar Pratiwi; Sugeng Dwi Riyanto (Jurnal Teknologi dan Sistem Komputer, 2017)
One of the important aspects in industrial field is a good material handling in logistics. Automated Guided Vehicle (AGV) can be an alternative to making an optimal logistics system. A widely used type of AGV based on its navigation system is line follower robot. This paper explains about applying the line follower robot integrated with LabVIEW to implement ultrasonic sensor as a radar to determine an empty space in logistic storage. The utilization of ultrasonic radar makes the searching process of empty space in the storage faster. Meanwhile, LabVIEW interface is used to help the operator to monitor material handling process. The result of the testing showed that ultrasonic sensor reading in Virtual Instrument LabVIEW has a good precision level when the line follower robot moves in a straight path. The error rate was 6,19% compared to the real situation.